Find out anything from anyone, anytime : secrets of calculated questioning from a veteran interrogator - Pyle, James O., 1950-; Karinch, Maryann (The Career Press, Inc., 2014)
"With his style of questioning alone, Jim Pyle can get more information than most other interrogators using multiple techniques."--Gregory Hartley, coauthor of the bestseller How to Spot a Liar The secret to finding out anything you want to know is amazingly simple: Ask good questions. Most people trip through life asking bad questions -- of teachers, friends, coworkers, clients, prospects, experts, and suspects. Even people trained in questioning, such as journalists and lawyers, commonly ask questions that get partial or misleading answers. People in any profession will immediately benefit by developing the skill and art of good questioning. Find Out Anything From Anyone, Anytime will give you the power to: -Identify and practice good questioning techniques -Recognize types of questions to avoid -Know the questions required when hearing unconfirmed reports or gossip -Practice good listening techniques and exploit all leads -Determine when and how to control the conversation -Gain real expertise fast Within professional interrogation circles, Pyle is known as a strategic debriefer -- meaning there is no one around him more skilled at asking questions and getting answers. He has been training other interrogators in questioning techniques since 1989